Farmer's lung in Devon. Issue 2 (April 1975) - Smyth, J T; Adkins, G E; Margaret, L; Moore, B; McWhite, E
Abstract : Farmer's lung is a cause of disability to agricultural workers in Devon and there is no evidence that the incidence is falling. A survey of known cases was made to assess the degree of disability in relation to the clinical history, the presence of farmer's lung precipitins, tests of lung function, and radiographic changes. Information was obtained about 200 patients diagnosed between 1939 and 1971. A survey of 148 of these patients showed that the disease was most commonly diagnosed in men aged 40 to 50 years and the most important symptom at diagnosis was dyspnoea related to occupational exposure to hay or grain. The onset was often insidious and only 67 patients (45%) were diagnosed during the first year of the disorder. Disability was severe in about one-third of the cases. The degree of disability did not seem to be related to the serological changes recorded either at diagnosis or at the time of our survey. Disability was commonly associated with restriction and reduced gas transfer factor and with airways obstruction in more severe cases. Many individuals reporting significant disability had only slightly abnormal ventilatory function tests at rest. Radiographic changes were found at survey in about one-third of the subjects reporting disability. Many farmers had not used an efficient mask. Treatment is unsatisfactory but steroid therapy is effective in acute episodes.